DEVELOPMENT AND RESEARCH OF JET PUMP-COMPRESSOR UNIT WITH PERIODICAL CONNECTION OF EJECTOR - Sazonov, Yuri; Mokhov, Mikhail; Gryaznova, Inna; Tumanyan, Khoren; Pyatibratov, Petr; Voronova, Victoria (Journal of Applied Engineering Science, 2020)
A new scientific approach to gas compression using jet pump-compressor units has been developed. The new patented technical solution offers an opportunity for the effective application of jet pump-compressor units for the compression of various gases up to pressures of 10...40 MPa.The purpose of the ongoing research work is to develop new scientific principles for gas compression using jet pump-compressor units. The new scientific approach is associated with the improvement of the pump-compressor unit, with the provision of conditions for the periodic connection of the ejector during the implementation of a cyclic low-frequency working process.The results of the research findings can be used to create energy-efficient technologies for the compression and pumping of various gases; it can be methane, associated petroleum gas, nitrogen, carbon dioxide, air, hydrogen or other gases. The creation of cheaper and more economical pump-compressor units will allow for the solution of urgent production problems in hydrocarbon production, including those in remote Arctic oil and gas fields.
Keywords: oil and gas production; ejector; compressor; pump; separator; research